2015
DOI: 10.1007/s00253-014-6328-9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the production of difficult-to-express full-length eukaryotic proteins using microbial cell factories: production of human alpha-galactosidase A

Abstract: 22Obtaining high levels of pure proteins remains the main bottleneck of many scientific and 23 biotechnological studies. Among all the available recombinant expression systems Escherichia coli facilitates 24 gene expression by its relative simplicity, inexpensive and fast cultivation, well-known genetics and the large 25 number of tools available for its biotechnological application. However, recombinant expression in E. coli is 26 not always a straightforward procedure and major obstacles are encountered when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
0
22
0
1
Order By: Relevance
“…Bacteria, in particular strains of Escherichia coli , have also been employed for this purpose, yet formation of protein aggregates as inclusion bodies and lack of post-translational modifications severely limit their applicability in producing recombinant enzymes for lysosomal ERT [227231]. Alternative bacterial systems such as Pseudoalteromonas haloplanktis have been used to generate active α-galactosidase, but their uptake and effect have not been demonstrated yet [232]. …”
Section: Lysosomal Enzyme Replacement Therapymentioning
confidence: 99%
“…Bacteria, in particular strains of Escherichia coli , have also been employed for this purpose, yet formation of protein aggregates as inclusion bodies and lack of post-translational modifications severely limit their applicability in producing recombinant enzymes for lysosomal ERT [227231]. Alternative bacterial systems such as Pseudoalteromonas haloplanktis have been used to generate active α-galactosidase, but their uptake and effect have not been demonstrated yet [232]. …”
Section: Lysosomal Enzyme Replacement Therapymentioning
confidence: 99%
“…Other signatures of cold adaptation are the psychrophiles-specific codon usage bias, that is involved in resistance to protein aging features involving asparagine cyclization and deamidation [10], and the high number of rRNA and tRNA genes, which might explain its translational efficiency even in cold condition [7]. This latter observation justifies an increasing use of Ph TAC125 in biotechnological applications, such as for the high quality production of recombinant eukaryotic proteins [1113]. This prompted a comprehensive characterization of this strains, through the analysis of its complete genome [7], its proteome in different conditions [14, 15], detailed growth phenotypes in complex media [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Almost 20 years ago, our research group suggested the use of Ph TAC125 and its derived genetic tools for the setup of a novel cell factory working at low temperatures [ 14 ]. Till then, much evidence highlighted the notable skills of the Antarctic bacterium in the high quality production of human and/or eukaryotic complex proteins, reinforcing our original idea [ 2 , 3 , 5 , 6 , 11 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 69%
“…The ability to produce heterologous proteins with high yields is a prerequisite for the exploitation of a microorganism as a cell factory [ 33 ]. The psychrophilic bacterium Ph TAC125 represents a model as a non-conventional host for the production of difficult to express proteins in a soluble and active form [ 2 , 5 , 34 , 35 ]. In the present paper, the set of plasmids for controlled gene expression in Ph TAC125 and KrPL—a pMtBL deficient strain—has been expanded with the IPTG-inducible plasmid pP79.…”
Section: Discussionmentioning
confidence: 99%